The Evaluation of Pelvic Cross Syndrome in Patients with Non-specific Chronic Low Back Pain - Amir Masoud A'rab; Mohammad Reza Nourbakhsh; Anoushiravan Kazem-Nezhad (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: The purpose of this study was the investigation of relationship between muscle imbalance syndrome in the lumbo-pelvic area (Pelvic Cross Syndrome) which includes the combination of weakness of phasic muscles and tightness of postural muscles, lordosis and chronic low back pain. Materials & Methods: This study was a comparative - cross-sectional and case - control research. A convenience sample of 600 subjects participated in this study. The size of lordosis, strength of abdominal and gluteal muscles and the extensibility of iliopsoas and back extensor muscles were measured in each group. The best cut-off values obtained from Receiver Operating Characteristic (ROC) curve analysis were used to categorize subjects as having weak or tight muscles in accordance with the assumptions. The lumbar lordosis in subjects with and without patterns of muscle impairments, and the association between lordosis and low back pain was assessed. Data were analyzed by using statistical methods such as: ICC, Kolmogroff - Smirnoff, Independent T test and ANOVA. Results: The Findings of this study showed no significant difference in the degree of lordosis in subjects with and without patterns of muscle impairment in pelvic cross syndrome (P=0.38) and no significant difference in the lordosis between subjects with and without low back pain among those with specific patterns of muscle impairment in pelvic cross syndrome (P=0.62). Data also showed no significant association between degree of lordosis and low back pain (P=0.25). Conclusion: The findings of this study did not support the Pelvic Cross Syndrome theory, which indicates certain patterns of muscle impairment would lead to exaggerated LL and LBP. Our data show a relationship between muscle impairment and occurrence of LBP, but probably not via changing the degree of lumbar lordosis as it has been proposed in PCS theory.